Applications of a New q-Difference Operator in Janowski-Type Meromorphic Convex Functions. (15th April 2021) - Ahmad, Bakhtiar; Khan, Muhammad Ghaffar; Aouf, Mohamed Kamal; Mashwani, Wali Khan; Salleh, Zabidin; Tang, Huo
Abstract : The main aim of the present article is the introduction of a new differential operator in q -analogue for meromorphic multivalent functions which are analytic in punctured open unit disc. A subclass of meromorphic multivalent convex functions is defined using this new differential operator in q -analogue. Furthermore, we discuss a number of useful geometric properties for the functions belonging to this class such as sufficiency criteria, coefficient estimates, distortion theorem, growth theorem, radius of starlikeness, and radius of convexity. Also, algebraic property of closure is discussed of functions belonging to this class. Integral representation problem is also proved for these functions.